THE INFLUENCE OF ACUTE DECOMPENSATION ON ONE-YEAR SURVIVAL AND MORTALITY IN PATIENTS WITH LIVER CIRRHOSIS - Curakova Ristovska, Elena; Genadieva-Dimitrova, Magdalena; Todorovska, Beti; Stardelova, Kalina Grivceva; Rankovich, Ivan; Milivojevich, Vladimir; Bogut, Ante; Janevski, Georgi (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Acute decompensation (AD) disposes important prognostic potential in cirrhotic patients, but the relation with the significant mortality predictors has not been fully investigated. We aimed to evaluate the influence of AD on the independent predictors of one-year mortality.  In 71 cirrhotic patients we analyzed the relation between AD and prognostic scores and indicators. We evaluated the independent association between several variables and one-year survival and their independent prognostic value for one-year mortality, before and after adjustment with the AD status.  AD patients (32) had significantly higher values of CTP, MELD, SOFA, and SAPS II scores, C-reactive protein (CRP), ferritin, leukocyte count, bilirubin, prothrombin time, INR, von-Willebrand factor and D-dimer concentration and lower values of vitamin D, hemoglobin, albumin, and sodium. MELD score (p=0.047), CRP (p=0.001), and vitamin D (p=0.014) were independently associated with one-year survival, while MELD score (p=0.010) and CRP (p=0.036) were independent predictors of one-year mortality. After adjustment with AD, MELD score was no longer independently associated with one-year survival and MELD score and CRP were no longer independent predictors of one-year mortality. AD has a strong influence on the variables independently associated with one-year survival and on the independent predictors of one-year mortality.